Comparison of Antioxidant Activity Based on Temperature Variables of Avocado Seed Extract from Maumere by 1,1-Diphenyl-2-Picrylhdrazy Method - Pratama, Mamat; Kusuma, Andi Trihadi; Rahmat, Sri Rahayu; Safitri, Dewi; Efendi, Nurmaya (Universitas Muslim Indonesia, 2024)
Avocados are plants that can grow well in tropical environments like Indonesia. People love this fruit because of its high antioxidant content and its delicious taste. The aim of this study was to measure the antioxidant activity of three extracts of ethyl acetate of avocado seeds (Percea americana Mill.) using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging method. The measurement was done using a quersetin as a reference standard with a maximum wavelength of 516 nm. The results of the study showed that the sample's half inhibitory concentration (IC50) value was 1,653.89 g/mL, 1,202.56 g/ mL, and 903.08 g/mL for two, four, and six hours, respectively.